If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(x + -6) = 6x + -54 Reorder the terms: -8(-6 + x) = 6x + -54 (-6 * -8 + x * -8) = 6x + -54 (48 + -8x) = 6x + -54 Reorder the terms: 48 + -8x = -54 + 6x Solving 48 + -8x = -54 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 48 + -8x + -6x = -54 + 6x + -6x Combine like terms: -8x + -6x = -14x 48 + -14x = -54 + 6x + -6x Combine like terms: 6x + -6x = 0 48 + -14x = -54 + 0 48 + -14x = -54 Add '-48' to each side of the equation. 48 + -48 + -14x = -54 + -48 Combine like terms: 48 + -48 = 0 0 + -14x = -54 + -48 -14x = -54 + -48 Combine like terms: -54 + -48 = -102 -14x = -102 Divide each side by '-14'. x = 7.285714286 Simplifying x = 7.285714286
| 8(x-8)+5=8x+6 | | C(x)=4x+170 | | 5(6x-7)=11+7x | | 1pint= | | 2v=-16 | | 4(x-4)-29=4x+2 | | 8=2x^2-24 | | 4x^2-48x+80= | | 37x+50-(x+25)=9(4x-2) | | 11r+60=6 | | -7v=-21 | | x/12=9.2 | | (x+13)(x+2)= | | -7y+3=25 | | X/2-4-12 | | -5/9=-7/3x | | k/6=12 | | 4tan(4x)=4 | | x-6x=46 | | -x^2+120-3276=0 | | 16-1/26(2x)=8-1/26(x) | | 4r-6=-12-2r | | 3(2x-5)=2(5+3x) | | x-y=200 | | 4(x+7)+3(3x-7)=72 | | (3x+4)(4x+1)-(2x+3)(x+3)=(5x+2)(2x+1) | | 14x-18=12-6x | | -4x-150=66-12x | | 0.19y+0.06(y+6000)=1860 | | 8x+16y=640 | | 3/4*b=8 | | 5s=4 |